1970
DOI: 10.1113/jphysiol.1970.sp009254
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of influx of calcium and strontium into rat intestine in vitro

Abstract: SUMMARY1. The role of uptake across the brush border in the intestinal absorption of calcium has been studied by examining the kinetics of influx into slices of rat intestine in vitro. Both mucosal and serosal surfaces were exposed to the medium.2. The rate of influx was accurately defined by a two-component expression comprising a saturable (Michaelis-Menten) term and a second term linear with concentration. Influx across the mucosal surface of closed sacs was similar, and the saturable component for slice in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 34 publications
3
25
0
Order By: Relevance
“…(13,14) However, Papworth et al proposed two routes of entry for the element: carrier-mediated and diffusionmediated. (15) With the exception of infants, it can generally be stated that strontium is absorbed to a lower extent than calcium, the strontium/calcium absorption ratio being ∼0.50. (16) The intestinal absorption of strontium increases under fasting conditions and is negatively affected by a high dietary content of calcium, phosphate, or chelating agents, such as sodium alginates, (17,18) which are of substantial interest in view of their ability to inhibit the intestinal absorption of the element in animals and man without affecting calcium absorption.…”
Section: Absorptionmentioning
confidence: 99%
“…(13,14) However, Papworth et al proposed two routes of entry for the element: carrier-mediated and diffusionmediated. (15) With the exception of infants, it can generally be stated that strontium is absorbed to a lower extent than calcium, the strontium/calcium absorption ratio being ∼0.50. (16) The intestinal absorption of strontium increases under fasting conditions and is negatively affected by a high dietary content of calcium, phosphate, or chelating agents, such as sodium alginates, (17,18) which are of substantial interest in view of their ability to inhibit the intestinal absorption of the element in animals and man without affecting calcium absorption.…”
Section: Absorptionmentioning
confidence: 99%
“…Like calcium (Ca), Sr is an alkaline earth metal (5). Previous studies have demonstrated homology between Ca and Sr absorption (4,6,7,8). Animal studies using radioactive Ca and Sr reveal the same kinetic influx pattern (7,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated homology between Ca and Sr absorption (4,6,7,8). Animal studies using radioactive Ca and Sr reveal the same kinetic influx pattern (7,8,9). Moreover, evidence suggests that the transport through enteral cells is mediated by the same membrane carriers (7,9).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations